Minat Pemuda terhadap Sektor Pertanian: Persepsi Faktor-faktor yang Berhubungan - Heryanto, Mahra Arari; Pardian, Pandi (Universitas Galuh, 2025)
The underrepresentation of young people in the agricultural sector is a pervasive phenomenon that has been observed across various continents. This phenomenon has significant consequences, including the underrepresentation of youth in the agricultural workforce and the subsequent aging of the sector's labor force. The factors that motivate young people to pursue careers in agriculture are multifaceted such as income opportunities, social status, government assistance, and the family environment. The objective of this paper is to identify the factors that influence youth interest in agriculture in paddy production center area. To this end, a questionnaire survey was conducted among youth who are children of rice farmers in Karangligar Village, Telukjambe Barat District, Karawang Regency and analyzed youth perceptions using Rasch Modeling. The results of the study indicate that strong factors that influence youth interest in the agricultural sector are social factors, farmer income, and land resources. The occupation of farmer is considered to have a great influence on society. Conversely, factors such as income, societal influences, family dynamics, and policy frameworks have been identified as deterrents to youth interest in pursuing careers in agriculture.The findings underscore the imperative for comprehensive support programs aimed at fostering interest and engagement among young people in the agricultural sector. Such initiatives should encompass the provision of adequate agricultural education, facilitation of business processes, and promotion of entrepreneurship, encompassing agricultural financing, production, and marketing of agricultural products.